2012
DOI: 10.1111/j.2042-7158.2012.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrosis effects of triterpene acids of Eriobotrya japonica (Thunb.) Lindl. leaf in a rat model of bleomycin-induced pulmonary fibrosis

Abstract: TAL had a positive prophylactic effect on lung fibrosis, which might have been related to its reduction on TNF-α or TGF-β1 expression in the alveolar macrophage of pulmonary fibrosis rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Loquat extracts have shown other bioactivities such as improvement of liver function [66,67], lung [68], renal [65] and neuronal cells [46], and also loquat extracts showed anti-obesity and hypolipidemic activity [36,37,69], anti-thrombotic potential [20], antiaging effects [70], anti-allergic [22], and antinociceptive activities [24], etc.…”
Section: Bioactivities Of Loquat Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loquat extracts have shown other bioactivities such as improvement of liver function [66,67], lung [68], renal [65] and neuronal cells [46], and also loquat extracts showed anti-obesity and hypolipidemic activity [36,37,69], anti-thrombotic potential [20], antiaging effects [70], anti-allergic [22], and antinociceptive activities [24], etc.…”
Section: Bioactivities Of Loquat Extractsmentioning
confidence: 99%
“…By using a rat model of bleomycin-induced pulmonary fibrosis, triterpene acids of loquat leaf showed antifibrosis effects by ameliorating the lung structure and alleviating fibrosis in the rat, where reduced expression of TNF- α and TGF-β1 both at the protein and mRNA levels were observed in the alveolar macrophage of pulmonary fibrosis rats [68]. The triterpene acids present in such loquat extracts included oleanolic acid ( 8 ), α-hydroxyoleanolic acid ( 34 ), arjunic acid ( 35 ), euscaphic acid ( 6 ), and ursolic acid ( 1 ), etc.…”
Section: Bioactivities Of Loquat Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover extract and isolated compound from leaves of this plant have been reported to be physiological active, exhibiting antioxidant, anti-inflammatory, antitumor, hypoglycemic effect, liver protective effect and antimutagenic (Banno et al, 2005;Bae et al, 2010;Cha et al, 2011aCha et al, , 2011bChoi et al, 2011). Moreover, antifibrosis effects of triterpene acids of Eriobotryae folium has been reported (Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Total triterpene acids possess various pharmacological activities, including antiinflammatory [1], anti-atherosclerotic and antidiabetic activity [2], anti-proliferative [3], and antifibrotic [4]. At the same time, research has shown that triterpene acids possess antioxidant activity [5].…”
Section: Introductionmentioning
confidence: 99%